[en] BRAZILIAN SECURITIES AND EXCHANGE COMMISSION AND THE MAIN LEGAL INSTRUMENTS USED TO REGULATE BRAZILIAN CAPITAL MARKET - JULIO RAMALHO DUBEUX (MAXWELL, 2006)
[pt] As últimas décadas têm se caracterizado pela intervenção estatal na economia mediante a atuação de diversas entidades administrativas reguladoras. A presente dissertação tem por objetivo analisar a estrutura legal da Comissão de Valores Mobiliários (CVM) e os principais instrumentos usados para a regulação do mercado de capitais brasileiro. Seguindo o modelo regulatório norte- americano, a CVM possui desenho institucional de entidade reguladora independente. A regulação que ela estabelece segue os princípios da política de disclosure. Para cumprir o seu papel, a CVM se vale de instrumentos regulatórios de natureza normativa, executiva e judicante. O estudo sugere que a credibilidade e a eficiência do mercado de capitais brasileiro dependem, em grande medida, da capacidade da CVM de conduzir a regulação do mercado. === [en] The last decades have been characterized by state intervention in the economy through the activities of various regulatory administrative entities. This dissertation aims to analyze the legal structure of Brazilian Securities and Exchange Commission (CVM) and the main instruments used to regulate Brazilian capital market. Following the North-American regulatory model, CVM is established as an independent regulatory entity. The regulation that it enacts follows the principles of disclosure policy. To fulfill its mission, CVM makes use of legislative, executive and adjudicatory regulatory instruments. This study suggests that credibility and efficiency of Brazilian capital market depend, largely, on the ability of CVM to conduct market regulation.